Disabilities and Disorders in Literature for Youth: A Selective Annotated Bibliography for K-12 - Crosetto, Alice; Garcha, Rajinder; Horan, Mark (Rowman & Littlefield Publishers, 2009)
One in every five Americans lives with at least one disability or disorder, including both the obvious, such as those requiring the use of a wheelchair, and the less evident ones, such as eating disorders or Asperger's syndrome. Those responsible for teaching disabled students and providing services and support for them need ready access to reliable and up-to-date resources. Disabilities and Disorders in Literature for Youth: A Selective Annotated Bibliography for K-12 identifies almost 1,000 resources to help educators, professionals, parents, siblings, guardians, and students understand the various disabilities and disorders faced by children today. This bibliography consists of four major headings_Emotional, Learning, Physical, and Multiple Disabilities_which are further categorized into works of fiction and nonfiction. Annotations provide a complete bibliographical description of the entries, and each entry is identified with the grade levels for which it is best suited and resources are matched with appropriate audiences. Reviews from recognized publications are also included wherever possible. Anyone interested in identifying helpful resources regarding disabilities and disorders will find much of value in this essential tool.